Coconut sector in India experiencing a new regime of trade and policy environment: A critical analysis - C. Thamban, K. Muralidharan, S. Jayasekhar, K.P. Chandran, (Journal of Plantation Crops, 2019)
Of late, Indian coconut sector is facing unprecedented crises on account of various macro and micro level factors. The productivity of the crop is constrained by low input use efficiency in conjunction with other biotic and abiotic stresses, which are priority areas of research. The aspect of mechanization also deserves adequate importance, considering the scarcity of skilled labour. Above all, the most important facet is value addition, which should be strengthened to mitigate the issue of low profitability of the sector. The post-World Trade Agreement (WTA) and ASEAN Treaty regime witnessed integration of plantation economies across the globe that resulted in fierce competition among producing countries. This paper addresses the pertinent issues on various facets of coconut economy by employing appropriate economic tools of analysis. The facets covered include trade aspects, global competitiveness, production economics, price analysis, policy level impediments and marketing issues. We have found that as far as the export markets of coconut value added products are concerned, India is comparatively a very small player with paltry export market shares. However, in recent times, Indian export sector has become vibrant with very high growth rate since Coconut Development Board (CDB) has been upgraded to the status of Export Promotion Council (EPC). Indian coconut sector has huge domestic demand, comparatively higher productivity, strong research support and technology delivery systems. In spite of these positive aspects, concerted efforts are lacking to effectively utilize the possible linkages between them for increasing the production and marketing efficiencies and enter the high value global chains. Sustainable coconut economy could only be achieved through integrated development of cultivation and industry coupled with a stable market.